Genetic Insights into Congenital Cardiac Septal Defects—A Narrative Review - Jorge L. Cervantes-Salazar; Nonanzit Pérez-Hernández; Juan Calderón-Colmenero; José Manuel Rodríguez-Pérez; María G. González-Pacheco; Clara Villamil-Castañeda; Angel A. Rosas-Tlaque; Diego B. Ortega-Zhindón (Biology)
Congenital heart diseases (CHDs) are a group of complex diseases characterized by structural and functional malformations during development in the human heart; they represent an important problem for public health worldwide. Within these malformations, septal defects such as ventricular (VSD) and atrial septal defects (ASD) are the most common forms of CHDs. Studies have reported that CHDs are the result of genetic and environmental factors. Here, we review and summarize the role of genetics involved in cardiogenesis and congenital cardiac septal defects. Moreover, treatment regarding these congenital cardiac septal defects is also addressed.